MO478FACTORS ASSOCIATED IN RAPID PROGRESSION OF CHRONIC KIDNEY DISEASE: A MULTICENTRE, RETROSPECTIVE COHORT STUDY. (29th May 2021) - Lee, Fei Yee; Islahudin, Farida; Wong, Hin-Seng; Bavanandan, Sunita; Mohd Tahir, Nurul Ain; Makmor-Bakry, Mohd
Abstract: Background and Aims: Identification of risk factors linked with rapid chronic kidney disease (CKD) progression is beneficial in shaping preventative and management strategies for maximal benefits out of the existing resources and capacity of care. To this end, the study aims to investigate the factors associated with rapid progression of CKD in the Asian population. Method: This multi-centre, retrospective cohort study recruited adult CKD patients of ≥18 years in two tertiary hospitals with a history of at least two years of Nephrology CKD clinic follow-up and with index eGFR, defined by the first identified estimated glomerular filtration rate (eGFR) during the study period, of ≥30 ml/min/1.73 m 2 . eGFR was calculated via CKD-EPI equation. Patients with less than three nephrology CKD clinic visits and outpatient eGFR values during the study period were excluded. Demographic data, clinical information, laboratory data and medication history were collected from the electronic medical records from January 2018 to March 2020. Annual slopes of eGFR change were quantified using linear regression of outpatient, non-emergency eGFR values, with a decline of >5ml/min/1.73m 2 /year defined as rapid CKD progression. Multiple logistic regression was used to identify factors associated with rapid CKD progression, in which variables with p ≤ 0.05 were considered as factors associated with rapid progression of CKD, followed by the examination of multicollinearity and correlation between the factors, and the use of the Hosmer-Lemeshow goodness-of-fit test, classification tables and area under the receiving operator characteristic (ROC) curve. Statistical analysis was performed using SPSS Version 23. Results: Among the 357 patients, 199 (55.7%) were men, median age was 61 years, while 105 (29.4%) patients had rapid CKD progression. The factors associated with rapid CKD progression after adjusting for possible confounding factors were Category A3 albuminuria (adjusted Odds Ratio [aOR] 2.217, 95% confidence interval [CI]: 1.241, 3.961), and adjustments to antihypertensives (aOR 1.158, 95% CI: 1.034, 1.296). Multicollinearity and interaction terms were not found, while the Hosmer-Lemeshow test (p=0.675), classification table (overall correctly classified percentage =69.8%) and area under the ROC curve (62.9%) were supportive of the model's fitness. Conclusion: Rapid CKD progression was observed among one-third of CKD patients in our practice setting. Category A3 albuminuria and adjustment to antihypertensives were factors of rapid CKD progression. Maladaptation from adjustments to antihypertensives might cause medication-related problems that might accelerate the progression of CKD. An alternative explanation is that adjustments were necessary because of poorly controlled hypertension which is a well-known risk factor for progressive CKD. Furthermore, with worsening kidney failure, hypertension becomes more difficult to control hence also necessitating medication adjustments. The findings could guide identification of CKD patients for enhanced pharmaceutical care and monitoring, especially when antihypertensives are adjusted, and during transition from hospitalisation to outpatient care.